An empirical investigation of the relevant forensic accounting skills exposure to the post- period of undergraduate accounting practical students / Mohamad Ridhuan Mat Dangi …[et al.] - Mat Dangi, Mohamad Ridhuan; Tajuddin, Norulhuda; Abd. Rashid, Mohd Zulfikri; Mat Bahari, Anis Barieyah (2014)
The demand for forensic accounting has drawn some attention due to the increases of fraud cases around the globe. The emerging and enhanced fraud activities involving the financial irregularities have made the forensic accounting investigation become important to the business and the public where it can be relied to solve problems, deter new problems, and contribute to new, tougher standards of corporate behavior and reported information. Thus, it is deemed important to have enough forensic accounting investigators equipped with the necessary skills related to their profession. This study is conducted to investigate whether the post-period undergraduate accounting practical students will consider the need for exposure of relevant forensic accounting skills to students. The respondents used for this study consist of 25 undergraduate students who have experiences during the practical training in audit, tax, and accounting firms. The findings revealed that most respondents are agreed with the forensic accounting skills needed as an exposure to the post-period undergraduate accounting practical students. This study also intended to open the mind of students about the importance of forensic accounting and its relevant skills in the future. This is depicted by more than half of the respondents stated their interest to be forensic accountant. It is expected that, by having an earlier exposure to the relevant accounting skill adopted in the universities, it can be a stepping stone to prepare a high competence forensic accounting investigators in the future.